Structure–Function Relationship of Novel Tetrakis (Mercapto-Terphenyl)Benzene Cobalt (II) Phthalocyanines: Synthesis and Computational Evaluation - Sevil Sener; Nursel Acar-Selcuki (Molecules, 2025)
This study introduces a newly synthesized Co(II) phthalocyanine complex (Co-Pc, 4) incorporating two (mercapto-terphenyl)thio-dione substituents, along with a detailed exploration of its structural, spectroscopic, and binding characteristics. The key precursor, 4-[(4′′-mercapto-[1,1′:4′,1′′-terphenyl]-4-yl)thio]phthalonitrile (compound 3), was first obtained and subsequently used to construct the phthalocyanine macrocycle through cyclotetramerization in the presence of cobalt and zinc salts under heat and vacuum in dimethylformamide. The resulting compounds (3 and 4) were characterized using a comprehensive array of analytical techniques, including elemental analysis, UV–Vis spectroscopy, FT-IR, 1H-NMR, and Q-TOF mass spectrometry. Additionally, density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations were employed to elucidate the electronic structure and geometrical features of Co-Pc 4, providing theoretical support for the experimental findings. The integration of theoretical and experimental findings provides in-depth insight into the electronic behavior and reactivity of compound 4, highlighting its promise as a candidate for photovoltaic applications. Further studies may investigate how structural modifications influence these properties, potentially leading to improved device performance.